2022
DOI: 10.3390/ijms23136973
|View full text |Cite
|
Sign up to set email alerts
|

Proscillaridin A Sensitizes Human Colon Cancer Cells to TRAIL-Induced Cell Death

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a cytotoxic cytokine that induces cancer cell death by binding to TRAIL receptors. Because of its selective cytotoxicity toward cancer cells, TRAIL therapeutics, such as recombinant TRAIL and agonistic antibodies targeting TRAIL receptors, have garnered attention as promising cancer treatment agents. However, many cancer cells acquire resistance to TRAIL-induced cell death. To overcome this issue, we searched for agents to sensitize cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Therefore, this system enables the rapid investigation of glycosides that can exhibit more functions or glycan structures that can give new functions to glycosides. For instance, it has been reported that proscillaridin A promotes cell death by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) via O-glycosylation 33 . It may be possible to enhance the anticancer effects of TRAIL therapeutics and increase their speci city for cancer cells by modifying the glycan structure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this system enables the rapid investigation of glycosides that can exhibit more functions or glycan structures that can give new functions to glycosides. For instance, it has been reported that proscillaridin A promotes cell death by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) via O-glycosylation 33 . It may be possible to enhance the anticancer effects of TRAIL therapeutics and increase their speci city for cancer cells by modifying the glycan structure.…”
Section: Discussionmentioning
confidence: 99%